HGG-04. USE OF AN ADVANCED RNA-SEQ FUSION PIPELINE RESULTS IN THE TARGETED TREATMENT AND SUSTAINED CLINICAL RESPONSE OF CHILDREN WITH RECURRENT PEDIATRIC HIGH-GRADE GLIOMA - Schwark, Kallen (Neuro Oncol, 2019)
BACKGROUND: Pediatric diffuse intrinsic pontine glioma (DIPG) and recurrent high-grade glioma (HGG) have an average progression-free survival (PFS) of 3 months. Gene fusions in cancer are being targeted with promising results. However, targeting fusions in DIPG and HGG has largely been unexplored – in part due to lack of clinical RNA-seq and/or low sensitivity in fusion calling. METHODS: We performed DNA sequencing (1700 genes) and RNA-seq analysis with the MI-ONCOSEQ CODAC fusion pipeline designed for improved fusion detection regardless of breakpoint within gene body. We identified three targetable gene fusions in patients with DIPG or recurrent HGG and retrospectively compared treatment and outcome to 19 patients with HGG and DIPG targeted with non-fusion DNA alterations. RESULTS: The first patient is an 11-year-old with anaplastic oligodendroglioma carrying a novel FGFR3-PHGDH fusion. The patient was treated with the FGFR inhibitor ponatinib, resulting in 24 months PFS. The second patient is a 15-year-old with a thrice recurrent mixed glioneuronal tumor despite multiple tumor resections and radiation; their tumor was found to carry a ROS1-GOPC fusion. The patient was treated with the ROS1 inhibitor entrectinib and remains progression-free after 44 months. The third patient is a 5-year-old with DIPG carrying a novel CTTNBP2-MET fusion who was treated with the MET inhibitor cabozantinib but passed away after 9 months from diagnosis (of note, tumor carried 15 other gene fusions). Our patients with HGG and targeted fusions had more favorable clinical response in comparison to our targeted non-fusion patients (12 months PFS) and historical controls (3 months PFS). CONCLUSIONS: RNA-seq analysis with advanced fusion calling can result in the identification of promising treatment regimens for DIPG and HGG. We also show that patients with targeted fusions have potential for superior clinical response in comparison to therapies targeting other alterations.